European banking enlargement, structural changes and recent developments - Olgu, Özlem 1979- (Palgrave Macmillan studies in banking and financial institutions, 2011)
Despite considerable progress on political and economic convergence over the last decade, financial structures of individual countries within the EU remain diverse. This book considers the future prospects of the banking industry in the context of enlargement, application of the IFRS and a potential new member country, Turkey.